2020
DOI: 10.1002/ajmg.a.62024
|View full text |Cite
|
Sign up to set email alerts
|

Two loss‐of‐function ANKRD11 variants in Chinese patients with short stature and a possible molecular pathway

Abstract: KBG syndrome is a rare genetic disease characterized mainly by skeletal abnormalities, distinctive facial features, and intellectual disability. Heterozygous mutations in ANKRD11 gene, or deletion of 16q24.3 that includes ANKRD11 gene are the cause of KBG syndrome. We describe two patients presenting with short stature and partial facial features, whereas no intellectual disability or hearing loss was observed in them. Two ANKRD11 variants, c.4039_4041del (p. Lys1347del) and c.6427C > G (p. Leu2143Val), were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In contrast, the only other variant with altered proteasome degradation, p.(Arg2585Cys), showed reduced proteasome degradation, and might slightly increase protein stability, although the latter was not statistically significant. The p.(Arg2585Cys) variant is also the only tested variant that resulted in reduced transcriptional repression on CDKN1A/P21 , consistent with previous observations for p.(Leu2143Val) [14]. These findings suggest that p.(Arg2585Cys) results in loss-of-function, despite a potential accumulation of mutant ANKRD11 that contrasts with the dosage reduction seen for the other tested variants.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, the only other variant with altered proteasome degradation, p.(Arg2585Cys), showed reduced proteasome degradation, and might slightly increase protein stability, although the latter was not statistically significant. The p.(Arg2585Cys) variant is also the only tested variant that resulted in reduced transcriptional repression on CDKN1A/P21 , consistent with previous observations for p.(Leu2143Val) [14]. These findings suggest that p.(Arg2585Cys) results in loss-of-function, despite a potential accumulation of mutant ANKRD11 that contrasts with the dosage reduction seen for the other tested variants.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by observations of reduced amounts of ANKRD11 mRNA and protein when the gene contains a PTV [12], suggesting that variants trigger the nonsense-mediated decay (NMD) pathway [12], although PTVs leading to a (partial) escape from NMD have also been described [7, 13]. Also consistent with haploinsufficiency is the finding that ANKRD11 mutated with p.(Lys1347del) or p.(Leu2143Val) shows reduced transcriptional activity on the p21 promotor in cell-based systems, and that this effect can be rescued by wildtype but not mutated ANKRD11 [14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The flow chart of the selected patients is shown in Figure 2 A. Only the KBGS patients with ANKRD11 gene variation were included ( n = 253) [ 2 , 5 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The types of variations included frameshift variation ( n = 158), nonsense variation ( n = 61), copy number variation ( n = 13), missense variation ( n = 13), splice site variation ( n = 6), and deletion variation ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenicity of a missense variation in the ANKRD11 gene needs to be considered cautiously; clinical phenotypes caused by other genes need to be excluded, and functional verification may be necessary. Zhang et al [ 50 ] found that a missense variation, c. 6427C > G (p.L2143V), in the ANKRD11 gene did not lead to abnormal expression of ANKRD11 protein and RNA, but could not restore the regulatory effect of P21 , which is an important factor in regulating cartilage differentiation. At present, only 13 cases of KBGS caused by missense variation of the ANKRD11 gene have been reported.…”
Section: Discussionmentioning
confidence: 99%